Hypophosphataemia after treatment of iron deficiency with intravenous ferric carboxymaltose or iron isomaltoside—a systematic review and meta‐analysis. Issue 5 (7th December 2020) - Schaefer, Benedikt; Tobiasch, Moritz; Viveiros, André; Tilg, Herbert; Kennedy, Nicholas A.; Wolf, Myles; Zoller, Heinz
Abstract : Aims: Hypophosphataemia is an increasingly recognized side‐effect of ferric carboxymaltose (FCM) and possibly iron isomaltoside/ferric derisomaltose (IIM), which are used to treat iron deficiency. The aim of this study was to determine frequency, severity, duration and risk factors of incident hypophosphataemia after treatment with FCM and IIM. Methods: A systematic literature search for articles indexed in EMBASE, PubMed and Web of Science in years 2005–2020 was carried out using the search terms 'ferric carboxymaltose' OR 'iron isomaltoside'. Prospective clinical trials reporting outcomes on hypophosphataemia rate, mean nadir serum phosphate and/or change in mean serum phosphate from baseline were selected. Hypophosphataemia rate and severity were compared for studies on IIM vs . FCM after stratification for chronic kidney disease. Meta‐regression analysis was used to investigate risk factors for hypophosphataemia. Results: Across the 42 clinical trials included in the meta‐analysis, FCM induced a significantly higher incidence of hypophosphataemia than IIM (47%, 95% CI 36–58% vs . 4%, 95% CI 2–5%), and significantly greater mean decreases in serum phosphate (0.40 vs . 0.06 mmol/L). Hypophosphataemia persisted at the end of the study periods (maximum 3 months) in up to 45% of patients treated with FCM. Meta‐regression analysis identified low baseline serum ferritin and transferrin saturation, and normal kidney function as significant predictors of hypophosphataemia. Conclusion: FCM is associated with a high risk of hypophosphataemia, which does not resolve for at least 3 months in a large proportion of affected patients. More severe iron deficiency and normal kidney function are risk factors for hypophosphataemia.